The evolution and practical application of time-motion analysis in rugby league - Laakso, L. A. (Journal of Australian Strength and Conditioning, 2020)
A variety of time-motion analysis methodologies have assisted practitioners objectively quantify the physical demands of both rugby league match-play and training. This narrative review focuses on both the evolution of time-motion analysis and its role in team field sports, as well as summarise and compare rugby league match-play and training data. Four electronic databases (CINAHL, Medline, Scopus, and SPORTDiscus) were searched from the earliest record to December 2019. 124 studies met the eligibility criteria and reported on the use of time-motion analysis in team field sports, in particularly, throughout rugby league match-play and training at an elite, semi-elite, amateur, and junior playing standard. This review demonstrated that training drills utilised to prepare rugby league athletes for the physical demands of match-play may not meet or exceed required demands. For instance, skill-based and speed and agility/repeated high intensity effort drills often fail to elicit match-play thresholds for physical demands such as absolute distance, speed, high-, very-high-speed, and sprint activity, as well as collisions and impacts. The strength and conditioning coach as well as sport scientist can utilise the data and findings presented within this review to increase the specificity of subsequent training methodologies. That is, if the aim of the training session is to replicate and/or overload match-play intensities, conventional training methodologies such as traditional conditioning drills and small-sided games are a more appropriate stimulus.